2012
DOI: 10.1152/ajpregu.00240.2012
|View full text |Cite
|
Sign up to set email alerts
|

CCL2 and CCL3 are essential mediators of pelvic pain in experimental autoimmune prostatitis

Abstract: Experimental autoimmune prostatitis (EAP) is a murine model of chronic prostatitis/chronic pelvic pain syndrome (CPPS) in men, a syndrome characterized by chronic pelvic pain. We have demonstrated that chemokine ligands CCL2 and CCL3 are biomarkers that correlate with pelvic pain symptoms. We postulated that CCL2 and CCL3 play a functional role in CPPS and therefore examined their expression in EAP. Upon examination of the prostate 5 days after induction of EAP, CCL2 mRNA was elevated 2- to 3-fold, CCL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
78
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(90 citation statements)
references
References 35 publications
5
78
0
Order By: Relevance
“…Our results showing almost complete prevention of UPK3A 65-84-induced tactile allodynia by genetic deletion of either CCL2 or its receptor CCR2 are similar to the findings of Quick et al (44) in C57BL/6J mice with experimental autoimmune prostatitis, suggesting a common mechanism in bladder-generated and prostate-generated pelvic allodynia. Furthermore, we showed that accumulations of activated, resting, and total Ϫ/Ϫ mice and Ccr2 Ϫ/Ϫ mice immunized with UPK3A 65-84.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our results showing almost complete prevention of UPK3A 65-84-induced tactile allodynia by genetic deletion of either CCL2 or its receptor CCR2 are similar to the findings of Quick et al (44) in C57BL/6J mice with experimental autoimmune prostatitis, suggesting a common mechanism in bladder-generated and prostate-generated pelvic allodynia. Furthermore, we showed that accumulations of activated, resting, and total Ϫ/Ϫ mice and Ccr2 Ϫ/Ϫ mice immunized with UPK3A 65-84.…”
Section: Discussionsupporting
confidence: 91%
“…A remaining question is whether the primary effects of Ccl2 and Ccr2 gene deletions in this EAC model were in mast cell recruitment and allodynia or in the initial immune response to UPK3A 65-84 immunization. In the experimental autoimmune prostatitis model of Quick et al (44), male Ccr2 Ϫ/Ϫ mice immunized with rat prostate lysate were completely protected from pelvic allodynia and exhibited only small, nonsignificant reductions in numbers of prostate-infiltrating CD4-positive and CD8-positive T cells compared with WT mice. In separate studies (21,25) of myelin oligodendrocyte glycoprotein peptide-induced experimental autoimmune encephalomyelitis, Ccl2 Ϫ/Ϫ mice and Ccr2 Ϫ/Ϫ mice on the C57BL/6 background exhibited less motor impairment than WT mice, but adoptive transfer of antigen primed T cells from the knockout mice to naïve WT recipients induced the disease phenotype.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Chemokine secretion has been evaluated in both semen and expressed prostatic secretion from men with prostatitis showing that CXCL5 and CXCL8 were elevated in expressed prostatic secretion from men with bacterial prostatitis, CPPS, and asymptomatic inflammatory prostatitis (10,44), chemokines that are both highly angiogenic and leukoattractant. In addition, CCL2 and CCL3 have also been postulated as biomarkers correlating with pelvic pain symptoms (45,46). However, the expression of CXCR3 or CCR6 ligands in prostate tissue from patients bearing CCPS has not been investigated to date.…”
Section: Discussionmentioning
confidence: 99%
“…Mice were tested for pelvic pain by a blinded tester as previously described by our laboratory [37; 38; 40]. Briefly, mice were habituated for one hour by placing them in individual plexiglass chambers (6×10×12 cm) on top of a stainless steel wire grid floor and suspended 2 feet above a flat surface.…”
Section: Methodsmentioning
confidence: 99%